Adsorption kinetics of Escherichia Coli on different Carbon Nanoforms - Md. Shamimul Haque Choudhury; Muhammad Athar Udding; Md. Nazmul Hasan; M. Shafiul Alam; M. Mamunur Rashid (Carbon: Science and Technology, 2012)
Adsorption of Escherichia coli (E. Coli) bacterial cells on different carbon nanoforms (i.e. Single walled carbon nanotube (SWCNT), Multiwalled Carbon nanotube (MWCNT), graphite and mixedFullerene) aggregates is studied. The diffusivities of pure cultures of E. Coli cells in SWCNT aggregates, MWCN aggregates, Graphite aggregates and Mixed Fullerenes was observed to be 1.5×10-9 cm2/s, 0.55×10-9 cm2/s, 0.8×10-9 cm2/s, and 1.016×10-9 cm2/s, respectively. In addition to batch adsorption studies, optical microscopy studies were also performed. The results suggest that diffusion kinetics ofbacterial cells depends on the concentration and average diameter of the nano-carbon aggregates and also on the type of material used. Diffusivity of E. Coli. in SWCNT was observed to be highest and isabout three times greater than for MWCNT, about two times greater than for graphite and about 1.5 times greater than for Fullerene aggregates. SWCNT seems to be best candidates (amongst the othermaterials studied) for adsorption of microorganisms – paying their way for application towards microorganisms filters and for biosensors (where it is desired to simultaneously detect and capture bio-threat agents).